Fungsionalisme Penanaman Tattwa Kualitas Pelaksanaan Yajña Bagi Generasi Muda Hindu Menurut Kesusastraan Dewa Tattwa - Anak Agung Gde Oka Widana; Ketut Lisnawati; Anak Agung Sri Sanjiwani (Jayapangus Press, 2023)
The yajña routine carried out by generations of Balinese Hindus seems to be synonymous with festivity, which ultimately becomes a paradox in religious life. Therefore, the younger generation of Hindus needs to be equipped with the philosophical meaning of the implementation of yajña through the basis of literature, in order to have a clear and directed basis or basis regarding their obligations in maintaining the preservation and sustainability of the yajña tradition in the space of religious spirituality. There are three things that become the basis of the problem in this research study, namely related to the structure of Dewa Tattwa literature, the tattwa of yajña quality contained therein, and the function of understanding the tattwa of yajña quality for the Hindu generation. The data studied in this qualitative research was collected through document recording techniques and literature, which in the process of analysis was carried out with qualitative descriptive techniques. The purpose of this study is to reveal the functional basis of instilling philosophical values in the implementation of yajña according to the Dewa Tattwa text for the younger generation of Hindus. The results of the analysis show the structure of the Dewa Tattwa text, including the formal structure (manggala, corpus, epilogue and language) and narrative structure (text theme and speech aspects). The yajña quality tattwa contained therein, includes religious tattwa (symbolic), spiritual moral tattwa, Hindu legal tattwa (awig-awig), and also legitimization tattwa (ratification or inauguration). Regarding the function of cultivating the quality of yajña implementation for the younger generation of Hindus according to Dewa Tattwa literature, including; educational function, rescue function, discipline function, decency function, and self-control function.